JTT-130, a Novel Intestine-Specific Inhibitor of Microsomal Triglyceride Transfer Protein, Reduces Food Preference for Fat - Yasuko Mera; Takahiro Hata; Yukihito Ishii; Daisuke Tomimoto; Takashi Kawai; Takeshi Ohta; Makoto Kakutani (Journal of Diabetes Research)
Microsomal triglyceride transfer protein (MTP) is involved in the assembly and secretion of triglyceride-rich lipoproteins from enterocytes and hepatocytes. JTT-130 is a novel intestine-specific MTP inhibitor, which has been shown to be useful in the prevention and treatment of dyslipidemia, obesity, and diabetes. JTT-130 has also been shown to suppress food intake in a dietary fat-dependent manner in rats. However, whether JTT-130 enables changes in food preference and nutrient consumption remains to be determined. Therefore, the aim of the present study was to investigate the effects of JTT-130 on food preference in rat under free access to two different diets containing 3.3% fat (low-fat diet, LF diet) and 35% fat (high-fat diet, HF diet). JTT-130 decreased HF diet intake and increased LF diet intake, resulting in a change in ratio of caloric intake from LF and HF diets to total caloric intake. In addition, macronutrient analysis revealed that JTT-130 did not affect carbohydrate consumption but significantly decreased fat consumption (P<0.01). These findings suggest that JTT-130 not only inhibits fat absorption, but also suppresses food intake and specifically reduces food preference for fat. Therefore, JTT-130 is expected to provide a new option for the prevention and treatment of obesity and obesity-related metabolic disorders.